IDENTIFYING UNIVERSITY STUDENTS' PERCEPTIONS OF 'ENGLISH' THROUGH METAPHORS - Cahit Erdem (Informascope, 2018)
This study aims to identify university students' perceptions of English through of metaphors. This is a qualitative study with phenomenological design. The data were collected from 342 first grade university students at a state university through a semi-structured form, in which the participants were asked to complete the sentence "English is like... because...". The data were analyzed through content analysis method. Besides identifying positive, negative and neutral metaphors, the data were also analyzed in terms of participants' gender, faculty and high school type as well as forming categories of metaphors based on their rationales. Some of the main results of the study include; more than half of the students created negative metaphors, male and female participants' percentages of positive and negative metaphors are close to each other, the faculties with the higher frequency of positive metaphors are faculties of technology, fine arts and law while the faculties with the higher frequency of negative metaphors are faculties of medicine, engineering and veterinary medicine. 15 different categories of metaphors are formed. The results of the study are expected to guide practitioners by informing them on students' perceptions of English and help them adjust teaching-learning practices.